2014
DOI: 10.1080/08905436.2014.895944
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Technological Properties of Lactic Acid Bacteria Isolated from Traditional Argentinean Goat’s Milk Products

Abstract: A total of 286 lactic acid bacteria isolated from goat's dairy products in northwest of Argentina were characterized. Lactobacilli (38%) and cocci (62%) were identified according to morphological, physiological, and relevant technological properties. L. plantarum (14%) and Enterococcus (34%) were the predominant species. S. thermophilus, Pediococcus and L. plantarum were the highest acid producers. Eight strains of L. fermentum produced bacteriocins or metabolites similar to bacteriocins. The API-ZYM test was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
3
7
0
2
Order By: Relevance
“…Tamang et al (2009) reported that high phosphatase activity of LAB strains showed their possible role in phytic acid degradation in fermented vegetables. In this study, acid phosphatase and phosphohydrolase activities were shown for most strains whereas weak alkaline phosphatase activities were detected in some strains, as similarly reported by Papamanoli et al (2003) for L. plantarum and Taboada et al (2014) for pediococci. Corroborating with the results of Taboada et al (2014), β-galactosidase activities of the tested lactobacilli (particularly L. brevis and L. buchneri) were generally higher than in pediococci.…”
Section: Enzymatic Profilesupporting
confidence: 65%
See 2 more Smart Citations
“…Tamang et al (2009) reported that high phosphatase activity of LAB strains showed their possible role in phytic acid degradation in fermented vegetables. In this study, acid phosphatase and phosphohydrolase activities were shown for most strains whereas weak alkaline phosphatase activities were detected in some strains, as similarly reported by Papamanoli et al (2003) for L. plantarum and Taboada et al (2014) for pediococci. Corroborating with the results of Taboada et al (2014), β-galactosidase activities of the tested lactobacilli (particularly L. brevis and L. buchneri) were generally higher than in pediococci.…”
Section: Enzymatic Profilesupporting
confidence: 65%
“…In this study, acid phosphatase and phosphohydrolase activities were shown for most strains whereas weak alkaline phosphatase activities were detected in some strains, as similarly reported by Papamanoli et al (2003) for L. plantarum and Taboada et al (2014) for pediococci. Corroborating with the results of Taboada et al (2014), β-galactosidase activities of the tested lactobacilli (particularly L. brevis and L. buchneri) were generally higher than in pediococci. α-galactosidase activity was generally absent or low in the tested strains, apart from some strains of L. brevis, L. buchneri and L. plantarum.…”
Section: Enzymatic Profilesupporting
confidence: 65%
See 1 more Smart Citation
“…El diseño de fermentos se realiza combinando las cepas que demuestran mayor aptitud en crecimiento y acidificación, como así también en sus capacidades proteolíticas y lipolíticas. Taboada et al (2014) caracterizaron también un total de 286 bacterias ácido lácticas aisladas de productos lácteos de cabra del noroeste argentino. Ancasi et al (2015) identificaron 128 levaduras y 39 lactobacilus en quesos frescos de cabra de la Quebrada de Humahuaca (Jujuy), los resultados obtenidos en este estudio muestran que la composición de las poblaciones de bacterias ácido lácticas y levaduras en quesos artesanales es específica de la región.…”
Section: I42 El Queso De Cabra Regionalunclassified
“…Varios autores (Mulvihill y Fox, 1977, 1978Visser y Slangen, 1977) mostraron en sistemas modelo que la degradación de caseína por cuajo se redujo, a valores de pH inferiores a 5,8. Por otro lado, las bacterias del ácido láctico, el grupo microbiano principal encontrado en el queso de cabra de la región noroeste de Argentina (Oliszewski et al, 2006;Taboada et al, 2014), tiene una ligera actividad en las caseínas intactas (Law et al, 1993) lo que también podría contribuir al bajo nivel de degradación en estos quesos durante la maduración. Se sabe que el contenido de sal y el método de salado afectan considerablemente la velocidad y/o extensión de la proteólisis, los altos niveles de sal se relacionan con un retraso en la proteólisis (Park, 2001).…”
unclassified